EMOTIONAL INTELLIGENCE AND CORONA-PHOBIA: THE MODERATING INFLUENCE OF AGE, FAMILY AND GENDER - Alebiosu, Yejide Olulani; Ogundokun, Moses Oluwafemi; Raji, Moromoke Nimota (Universitas Pendidikan Indonesia, 2022)
ABSTRACTApplication of emotional intelligence in daily activities is necessary in promoting positive relational and adaptive attitudes. This study explored emotional intelligence and corona-phobia and the moderating influence of the age, family and gender. It employed a descriptive survey research design and a total of two (200) hundred respondents participated in the study through the online monkey survey medium. The study adapted the Emotional Intelligence Scale (EIS) by Schutte, Malouff, Hall, Haggerty, Cooper, Golden and Dornheim (1998); Brief Family Relationship Scale by Moos and Moos, (1994); and the Collett-Lester Fear of Death Scale by Lester (2018) for data collection. The five (5) hypotheses raised were tested at 0.05 level of significance and data were analyzed using Pearsonâ€™s Product Moment Correlation and multiple regression. The study revealed that emotional intelligence has significant positive correlation on corona-phobia; it also confirmed the moderating influence of age, family and gender on corona-phobia while gender was the most potent influence. It was recommended that individuals should make deliberate efforts to build their skills on emotional intelligence as this facilitates individual coping ability with stress and its relatedness. Interventions for psychosocial preparedness were also suggested to reduce the negative impact that the outbreak of corona-phobia may have on individualâ€™s mental health.Â Keywords: phobia, corona-phobia, emotional intelligence, family, age, gender